ANALISIS KOMUNIKASI DIANTARA TRAVEL BLOGGER TENTANG KOTA MEDAN SEBAGAI TUJUAN WISATA - Rudy Irsian; Binur Napitupulu (Jurnal Ilmiah Akomodasi Agung, 2019)
This paper aims to analyze the communication that occurs between travel bloggers about the city of Medan as a tourist destination. The purpose of this study is to obtain a clear picture of the extent of the travel blogger writing that discusses tourist destinations in the city of Medan used as a reference for tourists to visit the city of Medan. The study was conducted with a qualitative descriptive approach based on content analysis theory. The results of this study can provide benefits and input for tourism businesses and the city government of Medan to participate in contributing information, facilities and infrastructure of tourist attractions in the city of Medan in particular.